SIMULATION OF NEUTRON ENERGY SPECTRA OF FILTERED THERMAL NEUTRON BEAM - Phù Chí Hòa; Phạm Ngọc Sơn; Huỳnh Thanh Sơn (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, simulation calculations of the energy spectra distribution of thermal neutrons transmitted through a filter section of sapphire and bismuth crystals were carried out. Techniques used sapphire and bismuth as neutron filters. The PHITS (Particle and Heavy Ion Transport System) simulation code was used to characterize the neutron energy spectra based on the material design parameters, geometrical structure, and shielding thickness.